Immune-Related RNA-Binding Protein-Based Signature With Predictive and Prognostic Implications in Patients With Lung Adenocarcinoma - Xu, Lei; Li, Wanru; Yang, Ting; Hu, Siqi; Zou, Qiong; Jiao, Ju; Jiang, Ningyi; Zhang, Yong (Frontiers in Molecular Biosciences, 2022)
Abstract Background: Dysregulation of RNA-binding proteins (RBPs) in cancers is associated with immune and cancer development. Here, we aim to profile immune-related RBPs in lung adenocarcinoma (LUAD) and construct an immune-related RBPs signature (IRBPS) to predict survival and response to immunotherapy. Methods: Correlation analysis was performed to establish a co-expression network of RBPs and immune-related genes (IRGs) to characterize immune-related RBPs in the TCGA-LUAD cohort (n=497 cases). Then, a combination of randomized survival forest (RSF) and Cox regression analysis was performed to screen RBPs and establish IRBPS. This was followed by independent validation of IRBPS in GSE72094 (n = 398 cases), GSE31210, (n = 226 cases), and GSE26939 (n = 114 cases), respectively. Differences between the low- and high-risk groups were compared in terms of gene mutations, tumor mutation burden, tumor-infiltrating lymphocytes, and biomarkers responsive to immunotherapy. Results: DDX56, CTSL, ZC3H12D, and PSMC5 were selected and used to construct IRBPS. The high-risk scores of patients had a significantly worse prognosis in both training and testing cohorts (P < 0.0001 and P < 0.05, respectively), and they tended to be older and have advanced TNM stage. Furthermore, IRBPS was a prognostic factor independent of age, gender, smoking history, TNM stage, and EGFR mutation status (P = 0.002). Besides, high-risk scores of IRBPS were significantly correlated with tumor-infiltrating lymphocytes (P<0.05). They also had a high level of PD-L1 protein expression (P < 0.01), number of neoantigens (P < 0.001), and TMB (P < 0.001), implying the possible prediction of IRBPS in the immunotherapy of LUAD. Conclusion: The currently established IRBPS encompassing immune-related RBPs might serve as a promising tool to predict survival, reflect the immune microenvironment, and predict the efficacy of immunotherapy among LUAD patients. Keywords: Lung adenocarcinoma, Immune-related RNA binding proteins, Overall survival, immune microenvironment, cancer immunotherapy